Trains, Trade, and Transaction Costs : How Does Domestic Trade by Rail Affect Market Prices of Malawi Agricultural Commodities? - Zant, Wouter (Published by Oxford University Press on behalf of the World Bank, 2019)
We measure the impact of low-cost transport by rail in Malawi on the dispersion of agricultural commodity prices across markets by exploiting the quasi-experimental design of the nearly total collapse of domestic transport by rail in January 2003 due to the destruction of a railway bridge at Rivirivi, Balaka. Estimations are based on monthly market prices of four agricultural commodities (maize, groundnuts, rice, and beans) in 27 local markets for the period 1998–2006. Market pairs connected by rail when the railway line was operational are intervention observations. Railway transport services explain a 14 to 17 percent reduction in price dispersion across markets. Geographical reach of trade varies by crop, most likely related to storability and geographical spread of production. Perishability appears to increase impact, reflecting limited scope for arbitrage. Overall, impacts are remarkably similar in size across commodities.